An acoustic study of Nigerian English vowels produced by hausa speakers / Maryam Ibrahim Ata - Maryam, Ibrahim Ata (2016)
This study aims at examining the Hausa speakers‘ production of English monophthong vowels from the acoustic point of view. The study focuses on native Hausa speakers of Northern Nigeria. Hausa language has 10 monophthong vowels, while English has 14 monophthong vowels; this shows clearly that there may be a disparity between English and Hausa in terms of vowels and sounds inventory. There are perceived differences between how the native speakers of English produce some of their monophthong vowels and how the Hausa speakers produce those same monophthongs. These differences may be because of vowel quality, duration, rhythm and accent of the speakers. It is not well understood how systematically the vowels of NigE are. Research on the acoustic measurements of NigE vowels is at dearth. In order to examine the vowels in NigE, monosyllabic words with CVC structure of the eleven (11) monophthong sounds in ‗hVd‘ and ‘bVd’ contexts were produced by ten (10) NigE. As a comparison, the pronunciation of English monophthongs was also done on 10 speakers, Malays speakers of English, 5 males and 5 females. Their age ranged from 24 to 40 years old. The recorded data were analyzed using PRAAT version 5.3.81 (Boersma and Weenik, 2014) phonetic software for instrumental analysis to measure the quality and quantity of vowels and the extent to which these vowels were phonetically contrasted between typically paired vowels. The findings from this study reveal that in both contexts, the vowels were produced almost similarly. However, in terms of vowel length contrast, all the vowels were differentiated between long and short, but lack of contrast is more apparent in vowel quality between the /ɪ/ - /iː/, /ᴧ/ - /ɑː/ and /ɒ/ - /ɔː/ vowel pairs.